2019
DOI: 10.1158/1078-0432.ccr-18-3900
|View full text |Cite
|
Sign up to set email alerts
|

The Hsp27-Mediated IkBα-NFκB Signaling Axis Promotes Radiation-Induced Lung Fibrosis

Abstract: Purpose: Lung fibrosis is a major side effect experienced by patients after lung cancer radiotherapy. However, effective protection strategies and underlying treatment targets remain unclear. In an effort to improve clinical outcomes, pharmacologic treatment of fibrosis is becoming increasingly popular; however, no ideal therapeutic strategy is yet available.Experimental Design: We used a mouse model to irradiate high focal (90 or 75 Gy) to 3-mm volume of the left lung. Lung tissues of mice were subjected to m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 49 publications
0
42
0
Order By: Relevance
“…In this study, we predominantly investigated the anti-fibrotic effects of LXA 4 -2 and 6 weeks after 75 Gy of IR-by immunostaining for α-SMA, TGF-β, and Twist and by MT staining for collagen expression. Two weeks after exposure to 75 Gy IR, our experimental model manifested radiation pneumonitis with radiation-induced inflammation, whereas 6 weeks after 75 Gy IR exposure, the model manifested IR-induced lung fibrosis with increased fibrosis marker and collagen expression 8,26,28 . To investigate the crosstalk between FPR2, IR-induced inflammatory responses, and fibrosis-related gene expression, we observed NF-κB and SBE promoter activity in the background of IR.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In this study, we predominantly investigated the anti-fibrotic effects of LXA 4 -2 and 6 weeks after 75 Gy of IR-by immunostaining for α-SMA, TGF-β, and Twist and by MT staining for collagen expression. Two weeks after exposure to 75 Gy IR, our experimental model manifested radiation pneumonitis with radiation-induced inflammation, whereas 6 weeks after 75 Gy IR exposure, the model manifested IR-induced lung fibrosis with increased fibrosis marker and collagen expression 8,26,28 . To investigate the crosstalk between FPR2, IR-induced inflammatory responses, and fibrosis-related gene expression, we observed NF-κB and SBE promoter activity in the background of IR.…”
Section: Discussionmentioning
confidence: 85%
“…Here, we examined the anti-inflammatory and anti-fibrotic properties of LXA 4 using a mouse model of RILI, wherein ablative radiation doses were delivered to the focal lung area using an image-guided IR system 6 , 7 , 26 28 . We also investigated whether LXA 4 regulates proteins that are important for EMT, particularly whether the crosstalk between LXA 4 -ALX/FPR2 and TGF-β/Smad signaling plays a key role in EMT.…”
Section: Introductionmentioning
confidence: 99%
“…In this report, we found that IR could induce the up-regulation of RAC1 expression and activity via activating the PI3K/AKT signaling pathway (36,(48)(49)(50). Interestingly, IRinduced EMT is regulated by RAC1, a member of the Rho family of small guanosine triphosphatases (GTPases) that has been shown to play a critical role in cytoskeleton reorganization, cell migration and cell survival (51,52). Thus, we raised the possibility that RAC1 might be an important regulator in the process of IR-induced EMT in lung cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Inhibition of HSP27 using a recently identified small-molecule inhibitor, J2, induces crosslinking of HSP27 attenuated RIPF development. Mechanism underlying HSP27-mediated fibrosis development is IkBa-NFkB signaling activation, which is involved in the EMT process ( Table 3 ) [ 103 ].…”
Section: Therapeutic Targets and Their Inhibitors In Ripfmentioning
confidence: 99%